IMPLEMENTASI KONSEP “SUSTAINABLE EVENT MANAGEMENT” DALAM PENGELOLAAN KEGIATAN MICE DI KAWASAN WISATA NUSA DUA, BALI - Pratiwi Arcana, Komang Trisna (Jurnal Master Pariwisata (JUMPA); Volume 01, Nomor 01, Juli 2014DO - 10.24843/JUMPA.2014.v01.i01.p05)
The growth of MICE (Meeting, Incentive, Conference, and Exhibition) Tourism and a requirement to incorporate the principle of sustainability in the management of tourism sector, bring such a concept of sustainable development for business which called as Sustainable Event Management. This study determines the characteristic of MICE Tourism and discovers the reason why Nusa Dua Resort, Bali, becomes a well known MICE tourism destination. Besides, it tries to obtain a clear picture as well as details on how the implementation of the concept of Sustainable Event Management and how it could improves the image of MICE tourism destinations in Nusa Dua Resort, Bali. This destination becomes an attractive tourist area and well known by its capability in handling national and international scale events. Therefore the management of MICE activities at Nusa Dua Resort Bali through implementation of the concept is expected to be even better and could be an example for the rest tourism destination in Bali especially for the sustainable management. This research uses qualitative method with data source collecting was purposive sampling and data collecting method by a combination of observation, interview, questionnaire, and documentation. The research findings describes that Nusa Dua Resort, Bali has MICE destination attributes to accommodate both of national and international scale event in term of: (i) accessibility; (ii) attraction; (iii) amenities and affordability; (iv) ancillary service; (v) special intermediaries; (vi) stakeholder support. Meanwhile implementation of Sustainable Event Management concept based on the checklist guidelines from UNEP (United Nations Environment Program) for Sustainable Event Guide, founds that the Professional Conference Organization (PCO), Destination Management Company (DMC) and MICE Management Team at Nusa Dua Resort beliefs it would bring such economic benefit for the company and gave a chance to involves local community to participate in many forms (employees, suppliers, entertainer), and also inspired their client and other stakeholder to behave in sustainable way. This study concludes that the implementation of the concept subsequently derived some impacts for local community and creates an image of the destination to the business traveler whose use the product itself.